Transcreation in the lyrics of songs : the foreign songs in Italian voices from Riccardo del Turco to Claudio Lolli - Velez, Antonino (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
There are different ways of translating popular songs or pop music. They can be translated for a volume that collects lyrics only to be read, to understand the meaning of the song’s message. If the song must be translated to be sung, for the performance, and you do not want to change the music, the only way to go is that of adaptation, in the appropriate choice of rhyming words that must adapt to the musical, mask (Low 2008). Our thesis, supported by three original case studies whose results we will study in the transition from a foreign language to Italian, is that this adaptation can coincide with what is now called transcreation.